Control interno de la Empresa “Centrograf” periodo 2020-2021. - Jiménez Figueroa, Damarys Tamara (2022)
Internal control is of paramount importance today in organizations, it is considered as the set of procedures, techniques and tools necessary for an evaluation of the company's operations and through the results to be able to correct errors and detect risks that arise in the company. normal activity of an organization with the objective of meeting the proposed goals, protecting its resources and promoting efficiency, effectiveness of operations, generating profitability, managing to maintain a stable position in the market before competitors. The case study was carried out with the objective of exposing the internal control of the company "CENTROGAF" period 2020-2021 to analyze its deficiencies if it meets the objectives and parameters established within the COSO system and its components: Control environment, Evaluation of risks, control activities, information and communication, survival and monitoring through the application of evaluation questionnaires to company employees about their roles and responsibilities around their work area and other aspects within the company. As a result of the analysis carried out, it was possible to verify the lack of policies and strategies, there are controls but they are not documented in a timely manner for their support, in addition, little verification of the records that are in accordance with the reports issued, internal communication is weak between the areas of the entity, finally, due follow-up is not carried out on recommendations or situations that could affect the entity in one way or another, to carry out internal control, the size of the company is not necessary, it is always important to have control procedures that allow minimizing the risks.